Corpo e movimento em turmas multi-idade na educação infantil: narrativas do cotidiano - Nunes, Natália de Borba (2023)
This research developed together with the Graduate Program in Movement and Rehabilitation Sciences at the Federal University of Santa Maria aims to understand how body and movement manifestations of children in a multi-age class of Early Childhood Education from multiple interactions among them, with adults, in different time-spaces. Still, we sought to: learn about the constitution and organization process of multi-age classes at the Ipê Amarelo Early Childhood Education Unit; to analyze how the thematic multi-age in Early Childhood Education has been addressed in scientific productions of Education; and identify and understand the manifestations of body and movement in the multiple interactions of children in multi-age classes from the perspective of the teachers. The qualitative methodological paths used in the investigation were: narrative research, which is concerned, through the stories told or written, in the analysis of the ways in which people give meaning to the world. Mention is also made of ethnographic inspiration through participant observation methods, the quantity and quality of records in a field diary and the intensity of interaction with the subjects in the researched context. A systematic review of the literature was carried out in order to analyze the incidence of the multiage theme in scientific productions in different sources. It is noteworthy that the research was approved by the Ethics Committee of the University, registered under the Certificate of Presentation for Ethical Appreciation nº 52119521.0.0000.5346/5.046.621. The time spend at the Unit, added to the readings of its scientific productions, associated with the literature on Narrative Research and experience, resulted in two main categories entitled “The times-spaces in everyday life at Ipê” and “The (trans)forming research methodological experience with children at Ipê Amarelo”. The analyzes showed the centrality and role of children in the Unit's daily life, in addition to the group's understanding that body and movement represent important expressive forms of children. In addition, a multi-age organization proved to enhance interactions and plays, by living with a diverse group. Finally, the formative process experienced by the researcher is highlighted in terms of methodological aspects of research with children and learning about childhood with children through the bond established with them and with adults in that context.